2020
DOI: 10.3390/antiox9080746
|View full text |Cite
|
Sign up to set email alerts
|

Germination Improves the Polyphenolic Profile and Functional Value of Mung Bean (Vigna radiata L.)

Abstract: The use of legumes as functional foods has gained increasing attention for the prevention and treatment of the so called non-communicable diseases that are highly prevalent worldwide. In this regard, biotechnological approaches for the enhancement of legumes’ nutritional and functional value have been extensively employed. In the present study, the process of germination increased several parameters of mung bean (Vigna radiata L.) functionality, including extract yield, total phenolic content and in vitro anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 71 publications
2
8
0
1
Order By: Relevance
“…e percentage of extracts always higher for MBG than for MBN regardless of the solvent used allows us to conclude that MBG has more bioactive molecules than MBN. Our results are in agreement with those of [25] who reported that the extraction yield increased with germination. Germination is then a process that leads to physicochemical changes and biochemical modifications that can increase the content of some biomolecules.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…e percentage of extracts always higher for MBG than for MBN regardless of the solvent used allows us to conclude that MBG has more bioactive molecules than MBN. Our results are in agreement with those of [25] who reported that the extraction yield increased with germination. Germination is then a process that leads to physicochemical changes and biochemical modifications that can increase the content of some biomolecules.…”
Section: Discussionsupporting
confidence: 94%
“…All these observations were confirmed and better appreciated by histological analysis. Reference [ 25 ] reported antiproliferative effects of mung bean extracts germinated for 48 hours, tested on different drug-resistant colon cancer cell lines, T84 and HCT-18, as well as on a non-tumorous CCD-18 line. Similarly, [ 38 ] showed that bioactive components of mung bean seeds have a wide range of activities such as anticancer, antihyperlipidemic, and antihypertensive activities.…”
Section: Discussionmentioning
confidence: 99%
“…Other nutrients in germinating beans also show similar trends; for instance, the γ-aminobutyric acid (GABA) content in germinating adzuki beans (Vigna angularis) showed increasing and decreasing, of which the highest content was at 48 h (37). The polyphenol content in germinating mung beans (V. radiata) also showed similar trends, and day 3 was the best time because it had the highest polyphenol content (45).…”
Section: Flavonoid Trends In Germinating Common Beansmentioning
confidence: 77%
“…Germination is a commonly used biotechnological process to enhance the digestibility of legumes, and the sprouts from legumes are regarded as important nutritious vegetables in daily diets nowadays. 136 It is reported that germination changes the nutritional values of mung bean in multiple aspects. First, the main macronutrients of mung bean, including carbohydrates, proteins, and fatty acids, are degraded during germination into easily digestible simple sugars, free amino acids, and organic acids.…”
Section: ■ Phenolic Profile Changes After Germination Of Mung Beanmentioning
confidence: 99%
“…Germination is a commonly used biotechnological process to enhance the digestibility of legumes, and the sprouts from legumes are regarded as important nutritious vegetables in daily diets nowadays . It is reported that germination changes the nutritional values of mung bean in multiple aspects.…”
Section: Phenolic Profile Changes After Germination Of Mung Beanmentioning
confidence: 99%